An Assessment of Agent-Based Modelling Tools for Community-Based Adaptation to Climate Change - Tom Selje; Rayhan Islam; Boris Heinz (Applied Sciences)
Human-induced climate change has highlighted the need for community-based adaptation (CBA) to build resilience in vulnerable communities. CBA empowers communities to leverage their resources and skills in shaping effective adaptation strategies. Agent-based modelling (ABM) is a suitable tool to develop tailored strategies that account for local capacities, priorities, and cultural contexts. This study assesses ABM tools for their suitability to model CBA, focusing on key criteria such as agent definition, sensitivity analysis, scalability, and experiment design. A comprehensive review of available ABM tools identifies NetLogo as the most fitting tool by its features, due to its flexibility in handling complex community–environment interactions. GAMA and Envision are nearly as suitable, offering robust support for modelling socio-economic and environmental dynamics. This article provides guidance for researchers and practitioners in choosing an appropriate ABM tool aligning with the specific needs of CBA, ensuring contextually relevant and sustainable adaptation solutions.